2021
DOI: 10.1016/j.arrct.2021.100130
|View full text |Cite
|
Sign up to set email alerts
|

Prism Adaptation Treatment Improves Inpatient Rehabilitation Outcome in Individuals With Spatial Neglect: A Retrospective Matched Control Study

Abstract: Objective To determine whether prism adaptation treatment (PAT) integrated into the standard of care improves rehabilitation outcome in patients with spatial neglect (SN). Design Retrospective matched control study based on information extracted from June 2017-September 2019. Setting Inpatient rehabilitation. Participants Patients from 14 rehabilitation hospitals scoring >0 on the Catherine Bergego Scale (N=312). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
2
18
2
Order By: Relevance
“…The implementation information being tracked included de-identified patient clinical records. Patient outcomes were reported separately (36,37).…”
Section: Participants and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation information being tracked included de-identified patient clinical records. Patient outcomes were reported separately (36,37).…”
Section: Participants and Settingmentioning
confidence: 99%
“…We evaluated the implementation outcomes using quantitative and qualitative information that was collected during the 4year period. The study also included collecting patient outcomes, which was reported separately (36,37).…”
Section: Implementation Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight of the relationship between PAT dosage and outcomes, the present study examined data gathered through regular clinical practice (i.e., clinical records) in 16 rehabilitation hospitals that participated in a large-scale implementation project for improving SN care of patients with brain injury (for details about the overarching project, see Hreha et al) 29 It is important to note that clinical records can provide practice-based evidence, which differs from evidence generated from prospective RCTs and has inherent limitations such as no blinding (i.e., the same therapists or colleagues on the same therapy team assessing and treating the same patients), no randomization or allocation concealment procedures assigning patients to control conditions, and a great heterogeneity of the sample. Nonetheless, as demonstrated in the matched, controlled study described above, 18 data based on clinical records can help answer certain questions and generate new research questions.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial neglect has a significant clinical impact as it hinders rehabilitation progress and outcomes [ 13 , 14 , 15 , 16 ]. Prism adaptation treatment (PAT) is one of the interventions that can reduce symptoms of spatial neglect and improve functional outcomes [ 17 , 18 ]. However, the results of randomized sham-controlled trials in stroke patients are mixed with respect to unequivocal benefits of this treatment for all stroke patients [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%